Characteristic of Pedada Fruit Starch and Pectin and Its Application as Edible Film Raw Materials - Galih Wendi Pradana; Agoes Mardiono Jacoeb; Ruddy Suwandi (Jurnal Pengolahan Hasil Perikanan Indonesia, 2017)
The synthetic packaging which commonly used so far has been generating new problems for health andthe environment. A safe packaging t which friendly environment is needed to be developed. One of them isedible film. Sonneratia caseolaris fruit has potential as raw material for edible film production, because itsavailability in nature is quite abundant as well as high starch and pectin content. The purpose of this studywas to determine the characteristics of starch and pectin from Sonneratia caseolaris fruit and determine theedible film characteristics produced by its starch and pectin. The starch extracted by water, then produced51.04% of total starch content (24.23% amylose and 26.81% amylopectin). The pectin extracted by 0.5%(w/v) ammonium oxalate solvent with 50 and 70 minutes as time variants. The results showed that starch andpectin with70 minutes of extraction tim) can be used as raw material in edible film production. Differencesin starch and pectin concentrations affected the edible film characteristics. Edible film with 4% starch, 1.5%pectin, and 1.5% glycerol showed the best characteristics of tensile strength, percent of elongation, watervapour transmission rate, and water vapour permeability.